Peculiarities of changes of psychophysiological functions, state of human adaptive capacity and stress resistance of students of higher medical institutions - Kalashchenko , S.I. (Medicni Perspektivi, 2021)
The study is devoted to assessing the psychophysiological adaptive capabilities of students of higher medical institutions. There was conducted a screening study on the basis of which a correlation analysis of a group of 42 students was performed. The main inclusion criterion was good physical activity. Exclusion criteria - the presence of chronic diseases, acute respiratory viral infections at the time of examination, taking antidepressants or psychoactive substances. The study was aimed to identify the peculiarities of changes in psychophysiological functions and the state of adaptive capacity of students of higher medical institutions being in stressful conditions. The following methods from the software and hardware complex "Psycholot-1" were used for the study: "Functional mobility of nervous processes according to Khilchenko" and "Memory." The survey was conducted under micro-stress, it means all tasks had to be completed in a limited period. Statistical analysis of the data was performed to establish correlations between psychophysiological indicators of short-term memory and functional mobility of nervous processes (Spearman’s rank correlation index). It was found that the faster the stimulus appears in conditions of time deficit, the lower the mobility of nervous processes in the student, which is directly reflected in the indicators in increasing the minimum exposure time of the figure on the screen (0.27±0.007 s). In addition, a relationship was found between the rate of reaction of the left hand to a stimulus and the amount of information that a person can store in short-term memory. The information obtained will help to determine the initial data of the adaptive capacity of a potentially healthy contingent of people and predict their success in further professional activities in the sphere of medicine.